2013
DOI: 10.1097/aog.0b013e3182a7f0d5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient Satisfaction With Michigan Four-Wall Sacrospinous Ligament Suspension for Prolapse

Abstract: Objective To describe patient satisfaction after Michigan four-wall sacrospinous ligament suspension for prolapse and identify factors associated with satisfaction. Methods Four hundred fifty-three patients were asked to rate their satisfaction with surgery and complete validated quality-of-life instruments. Postoperative support was extracted from the medical record and assessed when possible. Factors independently associated with patients who were “highly satisfied” were identified with multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 17 publications
3
16
0
1
Order By: Relevance
“…These observations provide a biomechanical explanation for why the hymen has emerged as an appropriate level both for defining symptomatic prolapse and for assessing surgical cure [24]. It is also consistent with the observation that women's dissatisfaction with surgical results increases once the vaginal wall is below the hymen, but not when it is at or above the hymen [25]. …”
Section: Discussionsupporting
confidence: 68%
“…These observations provide a biomechanical explanation for why the hymen has emerged as an appropriate level both for defining symptomatic prolapse and for assessing surgical cure [24]. It is also consistent with the observation that women's dissatisfaction with surgical results increases once the vaginal wall is below the hymen, but not when it is at or above the hymen [25]. …”
Section: Discussionsupporting
confidence: 68%
“…Other studies have commented upon the overall high objective and/or subjective success of uterosacral ligament suspension and/or McCall or modified McCall culdoplasty (20) and/or other restorative native tissue repairs, such as sacrospinous ligament suspension (21). In a systematic review of uterosacral ligament suspension, Margulies et al (22) described a pooled success rate (based on a definition of anatomic prolapse stage or grade <2 of 81.2% to 94.4% in all compartments, similar to our success rate at 5 years but with a different median follow-up length of 25 months.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similar to this study, several recent publications offer stronger evidence for improvement in quality of life: Larson et al reported high satisfaction rates eight years after sacrospinous ligament suspension, even in those women with pelvic floor defects at the hymenal ring after surgery. 26 Ulrich and colleagues reported that improvements in vaginal and sexual function depended on the type of repair, with patients undergoing levator plication reporting less benefit compared to women undergoing posterior prolapse repairs without levator plication 27 . Our study adds a large sample of highly characterized patients reporting improvement using standardized validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%